2020
DOI: 10.1126/science.aaz9649
|View full text |Cite
|
Sign up to set email alerts
|

The structure of human CST reveals a decameric assembly bound to telomeric DNA

Abstract: The CTC1-STN1-TEN1 (CST) complex is essential for telomere maintenance and resolution of stalled replication forks genome-wide. Here, we report the 3.0-angstrom cryo–electron microscopy structure of human CST bound to telomeric single-stranded DNA (ssDNA), which assembles as a decameric supercomplex. The atomic model of the 134-kilodalton CTC1 subunit, built almost entirely de novo, reveals the overall architecture of CST and the DNA-binding anchor site. The carboxyl-terminal domain of STN1 interacts with CTC1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
149
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(156 citation statements)
references
References 63 publications
7
149
0
Order By: Relevance
“…CST was identified as an RPA‐like protein complex due to its ssDNA‐binding ability and structural similarity to RPA (Miyake et al ., 2009; Lim et al ., 2020). Despite this similarity, recent discoveries on CST at stalled forks and DSBs suggest that CST is functionally distinct from RPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CST was identified as an RPA‐like protein complex due to its ssDNA‐binding ability and structural similarity to RPA (Miyake et al ., 2009; Lim et al ., 2020). Despite this similarity, recent discoveries on CST at stalled forks and DSBs suggest that CST is functionally distinct from RPA.…”
Section: Discussionmentioning
confidence: 99%
“…While our present data do not exclude the possible involvement of fill‐in synthesis in countering fork degradation, our results uncover a new function of CST in protecting fork stability and offer an alternative model that CST binds to ssDNA at reversed forks and directly inhibits MRE11 nuclease degradation, thereby protecting fork stability in a POLα‐independent manner (Fig 7D). Interestingly, while this manuscript was under review, the cryo‐EM structure of CST was reported, revealing that CST proteins are able to assemble into a decameric super complex when binding a 18‐nt ss telomeric oligo (Lim et al ., 2020). We speculate that if such or a similar structure can be formed at reversed forks, CST occupying 5’ overhangs may establish a physical barrier for MRE11 access to the 3’ end.…”
Section: Discussionmentioning
confidence: 99%
“…In budding yeast it is known as Cdc13-Stn1-Ten1 complex, however fission yeast lacks the CTC1/Cdc13 homolog, but contains Stn1 and Ten1 ( Martin et al, 2007 ). Recent cryo-EM structure of human CST reveals that it is capable of forming a decameric supercomplex when bound to telomeric ssDNA ( Lim et al, 2020 ). CTC1 is the largest subunit with a molecular weight of 134 kDa, and it possesses seven OB-fold domains ( Lim et al, 2020 ).…”
Section: Cstmentioning
confidence: 99%
“…Recent cryo-EM structure of human CST reveals that it is capable of forming a decameric supercomplex when bound to telomeric ssDNA ( Lim et al, 2020 ). CTC1 is the largest subunit with a molecular weight of 134 kDa, and it possesses seven OB-fold domains ( Lim et al, 2020 ). STN1 is 44 kDa and TEN1 is 13.8 kDa with one OB-fold each ( Figure 1A ; Rice and Skordalakes, 2016 ).…”
Section: Cstmentioning
confidence: 99%
See 1 more Smart Citation